Recent Advances of Bimetallic Sulfide Anodes for Sodium Ion Batteries - Huang, Yu; Xiong, Dongbin; Li, Xifei; Maleki Kheimeh Sari, Hirbod; Peng, Jianhong; Li, Yingying; Li, Yunyan; Li, Dejun; Sun, Qian; Sun, Xueliang (Frontiers in Chemistry, 2020)
The high usage for new energy has been promoting the next-generation energy storage systems (ESS). As promising alternatives to lithium ion batteries (LIBs), sodium ion batteries (SIBs) have caused extensive research interest owing to the high natural Na abundance of 2.4 wt.% (vs. 0.0017 wt.% for Li) in the earth’s crust with low cost. The high-performance electrode materials developing has been challenging to increase the feasibility of SIBs technology. In the past years, bimetallic sulfides (BMSs) with high theoretical capacity and outstanding redox reversibility have shown great promise as high performance anode materials for SIBs. Herein, the recent advancements of BMSs as anode for SIBs are reported, and the electrochemical mechanism of these electrodes are systematically investigated. In addition, the current issues, challenges, and perspectives are highlighted to address the extensive understanding of the associated electrochemical process, aiming to provide an insightful outlook for possible directions of anode materials for SIBs.